Управління прибутком на підприємствах хлібопекарської галузі - Легеза, Дар'я Георгіївна; Легеза, Дарья Георгиевна; Legeza, Daria (My University, 2018)
UK: У статті проаналізовано науково-теоретичні питання управління прибутком підприємств. Автор визначає основні особливості управління прибутком на підприємствах хлібопекарської галузі. Запропоновано основні підходи розподілу прибутку в умовах маркетингової товарної політики підприємства. Про-аналізовано економічні результати діяльності підприємств в залежності від умов розподілу прибутку. У дослідженні визначено вплив збутових витрат на рентабельність підприємств хлібопекарської галузі. EN: The paper presents the vital issues of income management, formed in a bakery, in Ukraine. The author opens up the market forces influencing on net income and their affecting on further profit formation. Income manage-ment plays an important role in economic status of enterprise and economics of a nation. While income forms the part of taxes, a state gets monetary funds from the taxes. In the last few years, there has been a growing interest in income formation, but scientists has shown a tiny interest in income sharing out which make a lot of Ukrainian enterprises nonprofit. A key limitation of this research is that lack of financial reports of bakery to make deep-in results. The aim of the issue is to examine income sharing in bakeries and to evaluate its efficiency according to marketing principles. Several practical questions arise when dealing with income management. It is important to identify the par-ticular ways of income sharing. It is a vital to reveal the main factors, which influence on income changing. It is key to predict an effect on enterprises profitability while size of income is diminishing. In this article the author explores the peculiar possibilities how distribution cost influence income. We used a new marketing approach to evaluate the distri-bution costs and profitability. The method was used on two regional bakeries, which have 15% of total market share in the South part of Ukraine. The analysis indicates that distribution costs do not meet volume of production to increase the market share. One of the surprised results of the research is that the more distribution cost managers spend, the more profitability the enterprise has. The finding was quite unexpected that the changings of assortment structure is directly proportional to profit changings. This paper is a modest contribution to the ongoing discussions about income management in bakeries and its effect on marketing activities.
Income management in bakery enterprises
Keywords: управління прибутком; хлібокомбінат; хлібопекарська галузь; витрати на збут; рентабельність; прибутковість; profit management; bakery; distribution costs; efficiency; profitability